Inhibitors of secreted phospholipase A2 suppress the release of PGE2 in renal mesangial cells - Vasilakaki, S.; Barbayianni, E.; Magrioti, V.; Pastukhov, O.; Constantinou-Kokotou, V.; Huwiler, A.; Kokotos, G. (Bioorganic and Medicinal Chemistry, 2016)
The upregulation of PGE2 by mesangial cells has been observed under chronic inflammation condition. In the present work, renal mesangial cells were stimulated to trigger a huge increase of PGE2 synthesis and were treated in the absence or presence of known PLA2 inhibitors. A variety of synthetic inhibitors, mainly developed in our labs, which are known to selectively inhibit each of GIVA cPLA2, GVIA iPLA2, and GIIA/GV sPLA2, were used as tools in this study. Synthetic sPLA2 inhibitors, such as GK115 (an amide derivative based on the non-natural amino acid (R)-γ-norleucine) as well as GK126 and GK241 (2-oxoamides based on the natural (S)-α-amino acid leucine and valine, respectively) presented an interesting effect on the suppression of PGE2 formation.